2021
DOI: 10.3390/ijms222111659
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Importance of Tyrosine Kinase Inhibitors against Cancer: Quo Vadis to Cure?

Abstract: GLOBOCAN 2020 estimated more than 19.3 million new cases, and about 10 million patients were deceased from cancer in 2020. Clinical manifestations showed that several growth factor receptors consisting of transmembrane and cytoplasmic tyrosine kinase (TK) domains play a vital role in cancer progression. Receptor tyrosine kinases (RTKs) are crucial intermediaries of the several cellular pathways and carcinogenesis that directly affect the prognosis and survival of higher tumor grade patients. Tyrosine kinase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 117 publications
0
16
0
Order By: Relevance
“…The regimen of cancer treatment is greatly modified by increasing the knowledge of molecular and tumour biology 6 . Noticeably, the selectivity of anticancer approaches has a low margin 7 . So, it is a serious concern to develop a new strategy of treating cancer that provides a high selectivity margin.…”
Section: Introductionmentioning
confidence: 99%
“…The regimen of cancer treatment is greatly modified by increasing the knowledge of molecular and tumour biology 6 . Noticeably, the selectivity of anticancer approaches has a low margin 7 . So, it is a serious concern to develop a new strategy of treating cancer that provides a high selectivity margin.…”
Section: Introductionmentioning
confidence: 99%
“…We downloaded IC 50 concentration Z scores from GDSC2 (Genomics of Drug Sensitivity in Cancer, dataset2) database (Iorio et al, 2016) for antitumor drugs that target key cancer-related cellular pathways (Figure 6B). We identified 4 compounds, AZ960 (Yang et al, 2010), JAK_8517, JAK1_8709 (Mongre et al, 2021) and Ruxolitinib (Han et al, 2018), that specifically target proteins in the JAK/STAT pathway and compared their drug sensitivity to PTPRM promoter methylation status in pancreatic cancer cell lines. We observed that drug sensitivity was significantly proportional to DNA methylation levels of the PTPRM gene promoter in pancreatic cancer cell lines (rho = 0.3, P = 0.00462) (Figure 6C) suggesting that PTPRM promoter methylation profiles maybe used as a potential biomarker for clinical treatment response in pancreatic cancer patient therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunctional RTKs result in developmental problems leading to diseases, including diabetes, atherosclerosis, and cancer. For example, RTKs are well-studied and targeted therapeutics for cancer [14] and diabetes [15]. Functional characteristics of organelles and cells are determined by the protein compositions at different physiological states [4].…”
Section: Membrane Proteins: Role In Diseases and Potential As Biomarkersmentioning
confidence: 99%